Fabrication and Optimization of Alginate Membranes for Improved Wastewater Treatment - Uzochukwu, John Sunday; Nkeiruka, Nweke Chinenyenwa; Odinaka, Nwachukwu Josiah; Olajide, Olufemi Gideon (Archives of Case Reports, 2025)
Alginate, a naturally occurring biopolymer extracted from brown algae, presents a promising avenue for developing sustainable and efficient membranes for wastewater treatment. This review comprehensively examines recent advancements in the fabrication, modification, and application of alginate-based membranes for effective water purification. The paper delves into various fabrication techniques, including casting, electrospinning, and 3D printing, which influence the structural and functional properties of the resulting alginate membranes. To enhance performance, strategies such as crosslinking, incorporation of porogens, and surface functionalization are employed. These modifications optimize crucial properties like mechanical strength, porosity, selectivity, and antifouling resistance. Furthermore, Response Surface Methodology (RSM) has emerged as a valuable tool for systematically optimizing fabrication parameters, enabling researchers to identify optimal conditions for achieving desired membrane characteristics. The integration of alginate membranes with biological treatment processes, such as phycoremediation (utilizing microalgae) and mycoremediation (employing fungi), offers a synergistic approach to enhance wastewater treatment efficiency. By immobilizing these microorganisms within the alginate matrix, their bioremediation capabilities are amplified, leading to improved pollutant degradation and nutrient removal. In conclusion, alginate-based membranes demonstrate significant potential as a sustainable and effective technology for wastewater treatment. Continued research and development, focusing on optimizing fabrication processes and exploring innovative integration strategies with biological systems, will further advance the application of alginate membranes in addressing the pressing global challenge of water pollution.